Measurement Invariance of the Pathological Narcissism Inventory and Multimethod Examination of Narcissistic Presentations in Community and Clinical Samples. (July 2023) - Di Pierro, Rossella; Costantini, Giulio; Fanti, Erika; Di Sarno, Marco; Preti, Emanuele; Madeddu, Fabio; Clarkin, John F.; Caligor, Eve; De Panfilis, Chiara
The Pathological Narcissism Inventory (PNI) is extensively used in recent empirical literature on pathological narcissism. However, most studies using the PNI are community-based, and no studies have used the PNI to investigate narcissistic presentations in personality disordered patients. This study investigates measurement invariance of the PNI in community participants and patients with personality disorders, and examines differences of narcissistic presentations in these samples through a multimethod approach. Results show that the PNI can be used reliably to measure and compare traits of pathological narcissism in community participants and patients with personality disorders. Personality disordered patients show higher traits reflecting vulnerable narcissism and overt manifestations of grandiose narcissism, compared with controls. Finally, network analysis indicates that traits of grandiose fantasies and entitlement rage have a central role in defining manifestations of PNI pathological narcissism, regardless of the presence of an underlying personality disorder. Research and clinical implications are discussed.